Penerapan Media Pembelajaran Berbantuan Canva Terhadap Minat dan Hasil Belajar Keterampilan Sepak Bola - Fernanda, Alfina Wahyu; Zhuka, Erika Mahardini; Agista, Yeskia Yudiana; Ridwan, Mochamad; Ishak, Asmadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Improving student interest and learning outcomes is often challenging in physical education learning, especially in motor skills such as passing the ball. The purpose of this study was to analyse the impact of the use of Canva-based learning media on students' learning interest and their passing skill outcomes. A mixed method was used in this study, with a quasi-experimental design using unequal pre-test and post-test control groups. The study population consisted of 114 students, with a sample of 70 students divided into two groups: an experimental group using Canva and a control group using conventional learning methods. Quantitative data were obtained through a passing skills test and a learning interest questionnaire, while qualitative data were obtained through in-depth interviews. Comparative statistical tests and thematic analysis for interviews were used to analyse the data to measure differences between groups. The results showed that the experimental group's learning interest and passing ability experienced a significant increase compared to the control group. The experimental group obtained an average score of 73.3 after the test, higher than the control group, which obtained 62.0. The average score of passing skill improvement in the experimental group was 15.9, higher than the control group, which obtained 13.6. It was concluded that motivation to use Canva's interactive visualizations increased, and understanding of passing techniques improved. Therefore, Canva improves students' motor skills and fosters their interest in physical education.